How to debate - Dunbar, Robert E. (Robert Everett) (New York : F. Watts, 1994)
An introduction to debating, including preparation and research of a topic, finding evidence, attacking opposing arguments, and giving an effective delivery.
Preparing for debate -- Methods of argument -- Making your delivery effective -- Taking the affirmative side -- How the negative attacks -- Listening to your opponent and responding effectively -- Methods of judging -- Types of debate.
Includes bibliographical references (p. 125), index, and glossary.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
7.2
Young Adult
Keywords: Debates and debating -- Juvenile literature; Debates and debating; Debates and debating